Effect of emotional picture viewing on voluntary eyeblinks. - Suvi Karla; Timo Ruusuvirta; Jan Wikgren (PLoS ONE)
Eyeblinks, whether reflexive or voluntary, play an important role in protecting our vision. When viewing pictures, reflexive eyeblinks are known to be modulated by the emotional state induced thereby. More specifically, the hedonic valence (unpleasantness-pleasantness) induced by the picture has been shown to have a linear relationship with the amplitude of a startle blink elicited during picture viewing. This effect has been attributed to congruence between an ongoing state and task demands: an unpleasant emotional state is assumed to bias our attention towards potentially harmful stimuli, such as startle tones. However, recent research suggests that the valence-specific modulation may not be limited to the sensory parts of the reflexive pathway related to startle responses. Here, we examined the effect of emotional picture viewing on voluntary (in response to a written command) eyeblinks in adult humans. Emotional modulation of startle blinks was also evaluated. We found that when viewing unpleasant pictures, the amplitude of reflexive eyeblinks was augmented, but the amplitude of voluntary eyeblinks was unaffected. Nevertheless, the response latencies of voluntary eyeblinks were found to be delayed during the viewing of pleasant and unpleasant relative to neutral pictures. We conclude that these results support the theory that emotional experience augments sensory processing specific to potentially harmful stimuli. Further, the emotional state seems not to exert an effect on voluntarily elicited motor activity.